Formalisation, informalisation and the labour process within the minibus taxi industry in East London, South Africa - Fobosi, Siyabulela Christopher (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
This thesis focuses on the labour process within the minibus taxi industry in East London, South Africa. This industry is structurally situated within the informal sector or economy but is marked by contradictory processes of formalisation and in-formalisation. Though the taxi industry seems to straddle the formal and informal economies in South Africa, the study is conceptually framed in terms of the informal sector but in a critically-engaged fashion. The very distinction between formal and informal economies, whether in South Africa or elsewhere, is open to dispute; and, even if accepted, there are differing conceptualisations of the relationship between the 'two' economies. Also, the conceptual clarity of the term 'informal economy' has been subject to scrutiny, given the vast range of activities it is said to incorporate. While the distinction between formal and informal economies may be a useful conceptual starting-point, this thesis demonstrates that it is analytically useful to speak of degrees and forms of formalisation and in-formalisation along a continuum, rather than to dichotomize economies. The thesis therefore analyses in depth the competing and tension-riddled processes of formalisation and in-formalisation in the minibus taxi industry, and with a specific focus on the labour process.
Keywords: Taxicab industry -- South Africa -- East London; Taxicab industry -- South Africa -- East London -- Personnel management; Informal sector (Economics) -- South Africa -- East London; Economics -- Sociological aspects; Industrial relations -- South Africa -- East London